Management of varicella in neonates and infants - Sophie Blumental; Philippe Lepage (BMJ Publishing Group, 2019)
In countries where vaccination is not implemented, varicella is a common ubiquitous disease offering a broad range of clinical presentations. Whereas mother-to-child perinatal transmission of varicella zoster virus (VZV) can lead to disseminated life-threatening diseases in unimmunised newborns, postnatal acquisition will be generally a source of milder infections. The pattern and severity of the disease are known to be partly determined by the timing of VZV acquisition during pregnancy with the highest risk period located around delivery. Management of youngest children after contact with a varicella case remains difficult for clinicians not only because of unawareness of varicella natural history and risks factors for serious complications, but also because of the lack of consensus from experts available in the literature. This state of uncertainty often leads to overconsumption of healthcare resources with systematic hospitalisation and unjustified antiviral intravenous therapies. After a concise literature review, this article proposes pragmatic recommendations considering newborns in various scenarios following a contact with VZV, taking into account the timing and mode of virus transmission, the maternal immunological status, the baby's gestational age and the presence of other underlying conditions.